PLANNING THICK RIGID PAVEMENT BY FAA METHOD ON THE NEW RUNWAY OF SUPADIO AIRPORT - Natalis Deni; Akhmadali Akhmadali; Siti Nurlaily Kadarini; Elsa Tri Mukti; Ferry Juniardi (Jurnal TEKNIK SIPIL, 2022)
Pontianak Supadio Airport is a gateway for exiting or entering tourists from within and outside the country. PT. Angkasa Pura II (Persero) plans to build a second runway at Pontianak Supadio International Airport to support economic growth and tourism in West Kalimantan. The method used in this study is the FAA (Federal Aviation Administration) method to determine the thickness of the rigid pavement to be used in planning the construction of a new runway. Forecasting the number of passengers and aircraft using the double moving average method. It is predicted that the plan period will be in 2035 with 12.763.479 passengers per year and 121.782 aircraft movements per year. Planned aircraft type Airbus A330-300 is an aircraft that requires the largest thickness of concrete slab with dual tandem wheel types, and MTOW 533.519 lbs. Due to the condition of the original soil which has a CBR value of 0.53%, a 52.5 cm thick embankment is required to achieve a CBR value of 6%. In the calculation of rigid pavement thickness planning for the design life of 2035, the surface course = 56,39 cm, subbase course = 15,24 cm, and stabilized subgrade / base soil = 52,5 cm for critical areas, and a surface course of 50,751 cm, subbase course = 13,716 cm, and stabilized subgrade / base soil = 52,5 cm for non-critical areas.